2017
DOI: 10.1038/srep39940
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index moderates the relationship between C-reactive protein and depressive symptoms: evidence from the China Health and Retirement Longitudinal Study

Abstract: The present study aimed to investigate the role of abnormal body mass index (BMI, kg/m2) in the depression-CRP (C-reactive protein) relationship in a healthy middle-aged and elderly Chinese population. Analytical samples were drawn from the China Health and Retirement Longitudinal Study (CHARLS), and participants were categorized by different BMI levels. Depressive subtypes were evaluated both at baseline and follow-up using the Center for Epidemiology Studies Depression scale. Hs-CRP and other variables were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 65 publications
(64 reference statements)
5
30
0
1
Order By: Relevance
“…The results of this study demonstrated that the respondents with lower BMI reported higher depression scores. Although many studies suggested that overweight or obesity is a risk factor for depression [51][52][53], our study results was consistent with one study based on population of China [54]. We found that the studies based on European and American sample population all reported the positive relationship between BMI and depression, but a few studies were reported in China.…”
Section: Discussionsupporting
confidence: 90%
“…The results of this study demonstrated that the respondents with lower BMI reported higher depression scores. Although many studies suggested that overweight or obesity is a risk factor for depression [51][52][53], our study results was consistent with one study based on population of China [54]. We found that the studies based on European and American sample population all reported the positive relationship between BMI and depression, but a few studies were reported in China.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, a nonsignificant negative association between depression and obesity has also been reported previously ( 12 , 43 ). In contrast, several studies reported a significant positive association between depression and obesity ( 11 , 12 , 20 , 21 , 44 , 45 ). Young people regarded thinness as a beauty symbol.…”
Section: Discussionmentioning
confidence: 81%
“…The association between obesity and depression has been normally studied in adolescents and the elderly population in China ( 19 21 ); yet there is a need to explore various indicators of obesity in detail. Hence, this large population-based cross-sectional survey was carried out to assess the potential relationship between depression and different body weight levels among the general population of Qingdao, China.…”
Section: Introductionmentioning
confidence: 99%
“…Higher levels of pro-inflammatory cytokines, Interleukin−1 beta (IL-1β), IL-6 and TNF-α were found in the blood or in the brain of these patients ( 21 , 27 , 28 ). Depression is also accompanied by an increase in acute phase proteins such as haptoglobin, α1-antitrypsin, ceruloplasmin, and C-reactive protein ( 27 , 29 ).…”
Section: Stress Depression and Inflammationmentioning
confidence: 99%